Strategies for Harmonic Mitigation in Water Pumping Systems Using Neutrosophic Logic - Jefferson A. Porras; Luis R. Curipoma; Byron P. Corrales; Jorge L. Villarroel (Neutrosophic Sets and Systems)
This study analyzed harmonic contamination in Quillán 1 and Quillán 2 pumping stations, characterizing the electrical system conditions and proposing solutions that addressed actual operational requirements. High levels of harmonic distortion were identified, particularly in 5th and 7th order harmonics, which exceeded the limits established by national regulations, despite the system presenting adequate energy utilization. To select the most appropriate mitigation strategy, the TOPSIS method under neutrosophic logic was applied, which allowed the integration of expert perception and the inherent indetermination margins of such systems. This logic, which simultaneously considers degrees of truth, falsehood, and uncertainty, enabled the evaluation of solutions without forced simplifications. The highest-rated option was the implementation of tuned passive filters, which were subsequently designed, simulated, and validated through specialized tools. The simulations demonstrated a substantial reduction of critical harmonics and a general improvement in power quality, ensuring regulatory compliance. The study highlighted the importance of using neutrosophic logic in combination with multicriteria decision methods as an effective resource for addressing complex electrical problems in real technical contexts, where absolute precision is not always possible or desirable.